ANALISIS FAKTOR-FAKTOR EKONOMI YANG MEMPENGARUHI EKSPOR TEH INDONESIA KE RUSIA - Stephany Dian Arbella (2022)
Agriculture commodities play an important role in international market demand, one of which is tea. Geographical conditions and highlands in Indonesia are very suitable for tea plants, so it would increase its international competitiveness when it develops. This research aims to determine the effect of production, areas, price, exchange rate, and GDP on Indonesia's tea exports. This research used quantitative data in a time series data of 60 samples from 2006-2020. Furthermore, this research used ARIMA to forecast with econometric aids Eviews 10. The results obtained include a positive and significant effect between production and export, and there is no effect on areas, price, the exchange rate, and GDP to exports. The forecasting results reveal that Indonesia's tea exports will fall in the next ten years